Transcripts abundance of TNP 1 and 2 genes in crossbred bull spermatozoa and insight into TNP2 3'-UTR polymorphism of the bta-miR-154 target site - Indrajit Ganguly; Jeevan C; Sushil Kumar; Sunil Kumar; DK Mandal; GK Gaur; Umesh Singh (Journal of Livestock Biodiversity, 2025)
Spermatogenesis involves a sequential replacement of histones with transitional nuclear proteins 1 and 2 (TNP1, TNP2),which are eventually replaced by porotamine 1 (PRM1) and protamine 2 (PRM2). These chromatin-remodeling proteinsmay decide organism's reproductive success by playing vital role in sperm formation and preserving sperm DNA integrity.The aim was to explore the transcript abundance of TNP1 and TPN2 genes in spermatozoa of normozoospermic (normal)and astheno-normozoospermic (motility impaired) Frieswal bulls semen as a footprint of successful spermatogenesisand gain insight into TNP2 3'-UTR polymorphism (g.1536 C > T) at the bta-miR-154 target site. While sperm from thenormozoospermic group showed higher levels of TPN2 mRNAs compared to astheno-normozoospermic, there was nosigniicant difference in transcript abundance (P>0.05) between groups. Almost comparable transcripts of the TPN1 genewere observed in both the groups (P>0.05). Screening of the SNP g.1536 C>T at 3'-UTR of TNP2, which alters the bindingto the bta-miR-154 seed sequence, revealed very high frequency of T allele in the populations (HF-0.81, FW-0.91 andJersey-0.97). The occurrence of frequent TT genotype and T allele in bulls probably indicates that functional seedsequence for bta-miR-154 at 3'UTR of TNP2 gene (due to the presence of T allele) might have selective advantagestowards regulation of TNP2 expression at testicular tissue and successful spermatogenesis. At the same time, it seemsthat the TT genotype does not affect differential TNP2 transcript abundance and sperm motility in mature spermatozoaof crossbred Frieswal bulls.